Chapter Estimating the Effect of Voters' Media Awareness on the 2016 US Presidential Election - Gallego, Maria (InTechOpen, 2019)
We examine whether voter media awareness of the 2016 US Presidential election campaign influenced the election using a logit model to estimate the probability that a voter with certain characteristics votes for one of the two candidates. Our results indicate that the more active voters were on social media, the more likely they were to vote for Trump, and the more aware they were of the electoral campaign (watching TV, listening to the radio, reading newspapers, etc.) and the more interested they were in the news/politics, the less likely they were to vote for Trump. The impact of these variables was not as important as their sociodemographic characteristics.